A conceptual model of a school–community collaborative network in enhancing coastal community resilience in Banda Aceh, Indonesia. (June 2015) - Oktari, Rina Suryani; Shiwaku, Koichi; Munadi, Khairul; Syamsidik; Shaw, Rajib
Abstract: Schools have an important role in knowledge development for building community resilience. It is important to involve the community with performing their roles to enhance resilience towards disaster, in order to ensure the sustainability of disaster education. This study aims to evaluate current efforts of disaster education and to develop a conceptual model for enhancing coastal community resilience. Qualitative and quantitative methodologies were used, including Focus Group Discussion and a questionnaire survey in 19 schools in Banda Aceh with a total of 634 respondents. The survey found that the school-based disaster preparedness (SSB) program was still effective in enhancing the resource mobilization capacity of teachers and students. But, in terms of obtaining knowledge from other sources, teachers in a SSB school have a lower percentage than teachers in a non-SSB school. This study also indicated some forms of collaboration that existed between school and community to improve school services. The results of this study proposed the School–Community Collaborative Networks (SCCN) model. The proposed model is expected to endorse the involvement of community in disaster education efforts and the use of a knowledge management strategy to provide individuals with a correct choice of action(s) to save lives. Also, the model hopefully can be used to promote transfer of knowledge from generation to generation as an important intangible asset to improve the sustainability, performance and innovation in resilience efforts.